Center of the universe - Hanlon, Abby (Hanlon, Abby. Dory Fantasmagory, 2025)
"Dory is on her first soccer team with her best friends, Rosabelle and George. She's ready to score a billion goals, but Rosabelle is having a meltdown over wearing cleats, and George is mysteriously acting like a baby. So, Dory attempts to befriend a new teammate, Valentina. But making a new friend isn't so easy, especially when Valentina kicks the ball perfectly every time, steals all the attention, and has a way of making a billion sound kinda small. Determined to outshine Valentina as the star of the team, Dory seeks help from her reliable imagination to flip the score. Complete with pencil-drawn pictures bursting with charm and character, this hilarious series about a lovably energetic little sister and her antics is sure to keep the whole family laughing."--